Multivariate rank-based forecast combining techniques - Matthias Klapper (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1999)
We analyze macroeconomic data using univariate and multivariate forecast combining techniques. We simulate forecast errors with different variance-covariance structures. The simulations are used to compare the performance of univariate and multivariate combining techniques.
Keywords: 519; Variance-covariance structure; simulation; combination of forecasts; multivariate combination of forecasts.; Prognoseverfahren; Multivariate Analyse; Theorie